Serine protease inhibitor from hemolymph of green mussel, perna viridis - Khan, M. S.; Goswami, U.; Rojatkar, S. R.; Khan, Mohammad Islam (Bioorganic & Medicinal Chemistry Letters, 2008)
Bioactivity guided fractions of cell-free hemolymph of bacterially challenged marine mussel, Perna viridis led to the isolation of a novel quaternary alkaloid 1, which was identified by its spectral data. The isolated molecule 1 has been found to be a potent serine protease inhibitor ( SPI) showing IC(50) and K(i) values of 102.5 and 97.1-104.68 mu M, respectively. The E(t)/K(i) value of SPI is 6.3, whereas E(t)/K(m) value is 1.04. The Van't Hoff analysis showed that the value of K(i) decreases with increase in temperature, and the binding of the inhibitor is entropically driven. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: hemolymph; Natural product; Perna viridis; protease inhibitor

Enhanced permeation, leaf retention, and plant protease inhibitor activity with bicontinuous microemulsions - Tamhane, Vaijayanti A.; Dhaware, Deepika G.; Khandelwal, Neha; Giri, Ashok P.; Panchagnula, Venkateswarlu (Journal of Colloid and Interface Science, 2012)
Bicontinuous microemulsions (BCMEs) have excellent solubulizing properties along with low interfacial tension and aqueous content that can be controlled. In this work, water soluble plant protease inhibitor (PI), well characterized for its activity against insect pests, was incorporated into a BCME system and explored for permeation on hydrophobic leaf surfaces and protease inhibition activity. The bicontinuous nature of the microemulsion containing water:2-propanol:1-butanol (55:35:10 w/w) was characterized using conductivity and self-diffusion coefficient measurements. The PI was soluble in the water-rich bicontinuous domains, stable in the microemulsions, and protease inhibition activity was retained for a prolonged duration. The microemulsions ensured greater wettability and a wider spread of the PI on hydrophobic leaf surfaces as revealed by contact angle measurements. Significantly, trypsin inhibition activity assays of the PI recovered from the leaves after delivery from the microemulsion indicated a significant increase in the PI retention on the leaf. This BCME enabled greater leaf permeation and retention of the PI can be attributed to a temporary disruption of the waxy leaf surface followed by self-repair without causing any long term damage to the plant. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Bicontinuous microemulsion; Biopesticide; Microemulsion pesticide; protease inhibitor; Protein encapsulation; Protein permeation

Sugar-amino acid cyclic conjugates as novel conformationally constrained hydroxyethylamine transition-state isosteres - Roy, Arup; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2012)
Hydroxyethylamine (HEA) isosteres have previously been shown to display a multitude of biomedical applications. In fact, the first protease inhibitor, saquinavir is an HEA based peptidomimetic. Herein we describe an easy-to-operate synthetic route to a series of carbohydrate-based conformationally constrained hydroxyethylamine (HEA) isosteres featuring amino acid side chains, starting from D-glucose. This class of novel sugar-amino acid-tethered conformationally restricted HEA systems may have bearing in practical application, particularly in the development of conformationally restricted protease inhibitors. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Conformationally constrained; D-Glucose; hydroxyethylamine isosteres; protease inhibitor; Reductive amination

Resistance through inhibition: ectopic expression of serine protease inhibitor offers stress tolerance via delayed senescence in yeast cell - Joshi, Rakesh S.; Tanpure, Rahul S.; Singh, Rajan Kumar; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2014)
Protease inhibitors have been known to confer multiple stress tolerance in transgenic plants. We have assessed growth of yeast (Pichia pastoris GS115) strains expressing inhibitory repeat domains (PpIRD(+)) of previously characterized Capsicum annuum protease inhibitors under high salt, heavy metal and oxidative stress. PpIRD(+) strains exhibited multiple stress tolerance and showed differential molecular responses at transcriptional and translational level on exposure to stress inducing agents like heavy metal, high salt and H2O2. PpIRD(+) strains display significant reduction in metacaspase (Yca1) activity, the key enzyme in apoptosis, indicates the possibility of cross reactivity of IRDs (serine protease inhibitor) with cysteine proteases. PpIRD(+) and Saccharomyces cerevisiae knockout with Yca1 (Delta Yca1) strain showed similar growth characteristics under stress, which indicated the delayed senescence due to cellular metacaspase inhibition. Molecular docking study showed a close proximity of IRDs reactive site and the active site of metacaspase in the complex that signified their strong interactions. Maintenance of GAPDH activity, primary target of metacaspase, in PpIRD(+) strain evidenced the inhibition of metacaspase activity and survival of these cells under stress. This report demonstrates a potential molecular mechanism of protease inhibitor-based multiple stress tolerance in yeast strains. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Metacaspase; Multiple stress tolerance; protease inhibitor; Yeast

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Tripeptides derived from reactive centre loop of potato type II protease inhibitors preferentially inhibit midgut proteases of Helicoverpa armigera - Saikhedkar, Nidhi S.; Joshi, Rakesh S.; Bhoite, Ashwini S.; Mohandasan, Radhika; Yadav, Amit Kumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2018)
Potato type II protease inhibitors (Pin-II PIs) impede the growth of lepidopteran insects by inhibiting serine protease-like enzymes in the larval gut. The three amino acid reactive centre loop (RCL) of these proteinaceous inhibitors is crucial for protease binding and is conserved across the Pin-II family. However, the molecular mechanism and inhibitory potential of the RCL tripeptides in isolation of the native protein has remained elusive. In this study, six peptides corresponding to the RCLs of the predominant Pin-II PIs were identified, synthesized and evaluated for in vitro and in vivo inhibitory activity against serine proteases of the polyphagous insect, Helicoverpa armigera. RCL peptides with sequences PRN, PRY and TRE were found to be potent inhibitors that adversely affected the growth and development of H. armigera. The binding mechanism and differential affinity of the RCL peptides with serine proteases was delineated by crystal structures of complexes of the RCL peptides with trypsin. Residues P1 and P2 of the inhibitors play a crucial role in the interaction and specificity of these inhibitors. Important features of RCL peptides like higher inhibition of insect proteases, enhanced efficacy at alkaline gut pH, longer retention and high stability in insect gut make them suitable molecules for the development of sustainable pest management strategies for crop protection.
Keywords: Helicoverpa armigera; Protease; protease inhibitor; Reactive centre loop peptides

Phyto-inspired cyclic peptides derived from plant Pin-II type protease inhibitor reactive center loops for crop protection from insect pests - Sailthedkar, Nidhi S.; Joshi, Rakesh S.; Yadav, Amit K.; Seal, Shubhendu; Fernandes, Moneesha; Giri, Ashok P. (Biochimica ET Biophysica Acta-General Subjects, 2019)
Background: Natural defence of plants against insect pests involves protease inhibitors (PIs) that interfere with insect digestive proteases. Pin-II type plant PIs are wound inducible upon insect damage and possess multiple inhibitory repeat domains that can inhibit trypsin and chymotrypsin-like proteases in the insect midgut. Yet, their agricultural ex-vivo application is limited due to large molecular size and environmental instability, which could be overcome by small peptides. Methods: Bicyclic peptides were designed by grafting Pin-II PIs derived reactive center loop (RCL) on synthetic tris(bromomethyl)benzene scaffold. In vitro binding with trypsin-like proteases was evaluated by biochemical and biophysical assays, followed by molecular dynamics simulations. In vivo effects on two major lepidopteran insect pests, Helicoverpa armigera and Spodoptera litura were studied upon feeding with peptide treated leaves. Affinity based pull down assays were used to identify target proteins in insect gut. Results: Bicyclic RCLs showed ten-fold enhanced protease inhibition compared to their linear counterparts. They exhibited feeding deterrence and growth reduction of lepidopteran insects. Bicyclic peptides predominantly interact with midgut serine proteases. Possible binding modes involve simultaneous interaction with the active site and specificity-determining residues of insect gut trypsin. Conclusion: Bicyclic peptides are potent inhibitors of serine proteases in the insect midgut. They cause feeding aversion and larval growth retardation. Bi-domain cyclic peptides interact with two sites on trypsin, leading to enhanced efficacy over linear RCL peptides. General significance: Bicyclic peptides mimic natural PIs by inhibiting insect proteases leading to growth reduction, thus, could be used as pest control molecules in agriculture.
Keywords: Cyclic peptide; Lepidoptera; Pest control; protease inhibitor; Reactive loop

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus